Smiles behind a mask are detectable and affect judgments of attractiveness, trustworthiness, and competence (2023)
Smiling is a popular and powerful facial signal used to influence how we are judged and evaluated by others. The recent COVID pandemic made the use of face masks common around the world. Since face masks, when properly worn, cover the lower half of the face, a common concern is that they inhibit our ability to signal to others through facial expressions like smiles. In this paper, we show through three subsequent studies that smiling faces are easily distinguished from neutral faces even if the person is wearing a face mask (Study 1, N = 1814). We further show that smiling behind a face mask significantly influences ratings regarding attractiveness, trustworthiness, and competence (Study 2, N = 250). We finally show that individuals with about 18 months of experience with face masks are well aware that smiling behind face masks will influence ratings regarding attractiveness and trustworthiness by others (Study 3, N = 94). Together, our studies provide evidence that face masks should not be seen as a threat that inhibits simple non-verbal communication through smiles.